PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENTS TEAM ASSISTED DIVISION PADA KELAS VIRTUAL - Frans, Syanet; Laurens, Theresia; Ngilawajan, Darma Andreas (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2023)
This study aims to determine the use of the Students Team Assisted Division (STAD) type of cooperative learning model in a virtual classroom and its effect on learning outcomes of limit algebraic functions in class XI students of SMA Negeri 12 Ambon. This type of research is descriptive quantitative with experimental type Post Test Only Control Group Design. The population in this study were all students of class XI IPA SMA Negeri 12 Ambon. The research sample was 31 students in class XI IPA 1 and XI IPA 2. The results showed that descriptively the average percentage of the implementation of learning by teachers was 67%, and (2) the average percentage of student activity in online learning was 64% and ( 3) the difference in the average value of the experimental class and the control class is 6.42. Based on the inferential statistical test with independent t sample test calculations, the Sig value was obtained. (2-tailed) = 0.031 smaller than the value which means there is a significant difference between the learning outcomes of the experimental class and the control class. This difference shows that the use of STAD type cooperative learning in online learning has a higher contribution than conventional online learning